New records of Cryptoblepharus cursor Barbour, 1911 (Squamata, Scincidae, Eugongylinae) from Java, Indonesia - Sugianto, Rizal Ananda; Iskandar, Djoko Tjahjono; Syamsudin, Tati Suryati (Check list (Luís Felipe Toledo), 2024)
he Lombok Snake-eyed Skink, Cryptoblepharus cursor Barbour, 1911 has been recorded in South Java prior to 1940. However, information on its population on the island are scarce. This study presents new records of C. cursor from Java. Visual Encounter Survey were conducted to observe habitat selections and collect skinks as voucher specimens. South Javan C. cursor are restricted to sandy littoral zones with Ipomoea pescaprae (L.) R.Br. - Spinifex littoreus (Burm.f.) Merr. whereas Lombok C. cursor are saxicolous, preferring rocky coasts. They also differ from the scansorial C. balinensis Barbour, 1911, a sympatric congener from Java.